Role ambiguity and corruption bureaucrat and apparatchik in African political systems - Le Vine, Victor T. (1994)
An important source of bureaucratic corruption in Sub-Saharan Africa lies in the blurring of the conventional distinctions between government officials - state bureaucrats - and officials of the ruling party (to use the Russian term, apparatchiki), particularly in the definition of their respective roles. This paper argues that insofar as government officials and apparatchiki both function to process and service the demands on the political-economic system, insofar as both operate as instruments of governance, members of the two groups come to see themselves not so much as components of parallel structures, but as parts of the same institutional nexus. In that. context, not only does it become difficult (for the state bureaucrats) to maintain normative fidelity to legally-defined roles, but both they and the apparatchiki will tend to redefine those roles to permit the use of the resources at their disposal to enhance their own and the ruling party's extractive capacities. Observation suggests that this is particularly true in so-called single party systems, somewhat less so in one-party dominant ones.
Keywords: Political corruption -- Africa; Africa -- Politics and government